Scopoletin: a review of its pharmacology, pharmacokinetics, and toxicity - Gao, Xiao-Yan; Li, Xu-Yang; Zhang, Cong-Ying; Bai, Chun-Ying (Frontiers in Pharmacology, 2024)
Scopoletin is a coumarin synthesized in diverse medicinal and edible plants, that plays a vital role as a therapeutic and chemopreventive agent in the treatment of a variety of diseases. In this review, an overview of the pharmacology, pharmacokinetics, and toxicity of scopoletin is provided. In addition, the prospects and outlook for future studies are appraised. Scopoletin is indicated to have antimicrobial, anticancer, anti-inflammation, anti-angiogenesis, anti-oxidation, antidiabetic, antihypertensive, hepatoprotective, and neuroprotective propertiesc, and immunomodulatory effects in both in vitro and in vivo experimental trials. In addition, it is an inhibitor of various enzymes, including choline acetyltransferase, acetylcholinesterase, and monoamine oxidase. Pharmacokinetic studies have demonstrated the low bioavailability, rapid absorption, and extensive metabolism of scopoletin. These properties may be associated with its poor solubility in aqueous medccia. In addition, toxicity research indicates the non-toxicity of scopoletin to most cell types tested to date, suggesting that scopoletin will not induce treatment-associated mortality nor abnormal performance within the test dose. Considering its favorable pharmacological activities, scopoletin has the potential to act as a drug candidate in the treatments of cancer, liver disease, diabetes, neurodegenerative disease, and mental disorders. In view of its merits and limitations, scopoletin is a suitable lead compound for the development new, efficient, and low-toxicity derivatives. Additional studies are needed to explore its molecular mechanisms and targets, verify its toxicity, and promote its oral bioavailability.